2008
DOI: 10.1007/s11706-008-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Apatite crystal in hard tissue of conodont fossils

Abstract: The present study was aimed at examining the nature of apatite crystal in the tooth apparatus of a conodont fossil using transmission electron microscopy (TEM), scanning electron microscopy (SEM), laser Raman microprobe spectrometry and electron-probe microanalysis (EPMA). The hard tissue of the condont consisted of 2 layers and the organization varied with the size of the crystal. Higher magnification showed that the crystals were observed in the lattice of (100) and the central dark lines were not present. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…One pathway, mediated by the precursor mineral octacalcium phosphate (OCP), may have appeared around the Cambrian period 45) . This OCP pathway is facilitated by the presence of F ions 46) that contribute to the creation of fluorapatite observed in the tooth apparatus of conodonts, fish enameloid, and other structures according to previous reports 45,[47][48][49][50] . The other pathway involves CDL formation, which may have evolved up to the Silurian period 45) and is observed in ordinary hard tissues such as tooth enamel, dentin, and bone 29,30,51,52) .…”
Section: Comparison Of Enzymatic Activity Between F-and Cd-exposed Enmentioning
confidence: 82%
“…One pathway, mediated by the precursor mineral octacalcium phosphate (OCP), may have appeared around the Cambrian period 45) . This OCP pathway is facilitated by the presence of F ions 46) that contribute to the creation of fluorapatite observed in the tooth apparatus of conodonts, fish enameloid, and other structures according to previous reports 45,[47][48][49][50] . The other pathway involves CDL formation, which may have evolved up to the Silurian period 45) and is observed in ordinary hard tissues such as tooth enamel, dentin, and bone 29,30,51,52) .…”
Section: Comparison Of Enzymatic Activity Between F-and Cd-exposed Enmentioning
confidence: 82%
“…F in natural mineral of fluorapatite showed 3.831 ± 0.061 wt% 22) . Enameloid of blue sharks showed 3.047 ± 0.360 wt % of F content 11,22) , though all sharks have fl uorapatite crystal 23) . Mature tooth of cichlid enameloid crystals showed 3.2% fl uoride content 23) .…”
Section: Discussionmentioning
confidence: 98%
“…Smith reported that enameloid was a more recent phylogenetic development than enamel 10) . However, the phylogenesis origin of the enamel and enameloid, is still under discussion [11][12][13] . Furthermore, the ultrastructure of the enamel apatite in Eusthenopteron is not well known 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, hard tissue-forming cells-such as ameloblasts, odontoblasts and osteoblasts-are responsible for the development of various sized apatite crystals suited to different hard tissues (e.g., large crystals in enamel and small crystals in dentin and bone). In addition, the process of crystal formation under normal conditions is strictly regulated by cellular activities that either produce crystals with CDLs in various hard tissues [23][24][25][26][27][28] or without CDLs in the tooth enamel of fish and tooth apparatus of conodonts 29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…According to our recent findings, apatite crystals can be crystallographically divided into 2 types: (1) crystals with central dark lines (CDLs), formed in normal calcified hard tissues of vertebrates [23][24][25][26][27][28] , and (2) crystals without CDLs, formed, for example, in the tooth enamel of fish and tooth apparatus of conodonts 29,30) . Hard tissue-forming cells thus either produce crystals with CDLs or without CDLs.…”
Section: Introductionmentioning
confidence: 99%